Sustainable Growth in Global Markets Strategic Choices and Managerial Implications - Rajagopal (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
Sustainable Growth in Global Markets provides a comprehensive introduction to the concept of market and business management outside the domestic market. It covers complex elements of market management, analysing behavioural theories such as theory of comparative advantage, theories of macro and micro marketing economics, socio-cultural theories, and various contemporary concepts of international business management. The book puts forward a broad foundation of the subject beginning with a discussion of the concept of market dynamics and followed by an analysis of the changing behaviour of markets and its components. The core discussion focuses upon the ability to do business in international markets, putting forward critical insights on the significance of leadership, building consumer value through innovation, tracking the external environment for organizational change as well as important emerging trends towards building an innovative venture.